Prostaglandin E2 as a read out for endotoxin detection in a bovine whole blood assay. Issue 2 (1st August 2014) - Wunderlich, C.; Schumacher, S.; Kietzmann, M.
<x xml:space="preserve">Abstract</x> The detection of endotoxin contamination is an essential part of drug safety testing. The rabbit pyrogen test (RPT), the limulus amoebocyte lysate (LAL) test, and the monocyte activation test (MAT) are established methods for the detection of pyrogens. However, the RPT is insufficiently standardized; the LAL test is solely capable of identifying the presence of endotoxins, whereas the use of the MAT is limited by the availability of human blood. Here, we introduce a new procedure for testing endotoxin contamination using prostaglandin E2 (PGE2) release from bovine whole blood. We incubated bovine whole blood overnight with lipopolysaccharide (LPS) from Escherichia coli 0111:B4, concentrations ranging from 1.56 to 12.5 pg/mL, and found significantly increased PGE2 production for even the lowest LPS concentrations. Testing the possibility of storing the blood at 4 °C before use also yielded positive results as 1.56 pg/mL still significantly increased PGE2 production, thus suggesting some flexibility of the assay regarding time. These results emphasize the potential of using bovine whole blood for highly sensitive endotoxin testing. As a perspective, currently ongoing research aims to show whether the assay is also capable of detecting nonendotoxin pyrogens.